ANALYSIS OF ECONOMIC INDICATORS FOR OIL FLAX PROCESSING - E. V. Novikov; N. V. Basova; A. V. Bezbabchenko (Сельскохозяйственные машины и технологии, 2018)
Oil flax grows in many countries of the world. Fibre production on its basis can significantly increase the profitability of flax-growing farms. At the present stage, taking into account the real possibilities of the national economy, for its effective development  it is necessary to introduce advanced technologies. Cur-rently, processing enterprises may choose among different technological equipment lines to process oil flax into fibre and thus get additional profit. (Research purpose) The determination of a technologically and economical-ly effective line for oil flax processing. (Materials and methods) The main materials for calculation were represent-ed by the indicators of production capacity, the average annual value of fixed as-sets, the amount of money spent on salaries and wages, etc. The main research method is the balance method that allows making a plan in the form of a balance sheet that takes into account the sources of inputs and the requirements for these inputs. (Results and discussions) The authors have considered low-cost lines for oil flax processing into short fibre on the basis of disintegrators of various brands (from domestic and foreign producers), offered characteristics of the fibre obtained in the lines, and analyzed technical and economic indicators of various technologi-cal lines under different conditions, and the payback period of capital expenditures for different oil flax acreages. (Conclusions) The authors have determined that the most effective is the pro-cessing of oil flax from an area of at least 1000 hectares, with a throughput capaci-ty of raw materials of at least 1000 kg/h and a distance of the transportation of straw rolls to a processing site of 50 km. They have also obtained technological and economic data that can be used in the organization of oil flax processing into marketable fibre.